In vivo comparison of the charge densities required to evoke motor responses using novel annular penetrating microelectrodes - Brunton, Emma K.; Winther-Jensen, Bjorn; Wang, Chun; Yan, Edwin B.; Hagh Gooie, Saman; Lowery, Arthur J.; Rajan, Ramesh (Frontiers in Neuroscience, 2015)
Electrodes for cortical stimulation need to deliver current to neural tissue effectively and safely. We have developed electrodes with a novel annular geometry for use in cortical visual prostheses. Here we explore a critical question on the ideal annulus height to ensure electrical stimulation will be safe and effective. We implanted single electrodes into the motor cortex of anesthetized rats and measured the current required to evoke a motor response to stimulation, and the charge injection capacity of the electrodes. We compared platinum iridium electrodes with different annulus heights, with and without a coating of porous titanium nitride. Threshold charge densities to evoke a motor response ranged from 12-36 µC.cm^-2.ph^-1. Electrodes with larger geometric surface areas required higher currents to evoke responses, but lower charge densities. The addition of a porous titanium nitride coating did not significantly influence the current required to evoke a motor response. The charge injection capacity of both electrode types was significantly reduced in-vivo compared with in-vitro measurements. The measured charge injection capacity was 72 and 18 µC.cm^-2.ph^-1 for electrodes with and without a titanium nitride coating respectively. These results support the use of platinum iridium annular electrodes with annulus heights greater than 100 µm (geometric surface area of 38, 000 µm^2). However, if the electrodes are coated with porous titanium nitride the annulus height can be reduced to 40 µm (geometric surface area of 16,000 µm^2).